Organización contable en la empresa del Sr. Guerrero Luzuriaga Luis Eduardo del cantón Catamayo, periodo del 01 de octubre al 31 de diciembre del 2023 - Nole Guerrero, Estefania Anabelle (2024)
The present Curricular Integration Work aims to analyze the financial situation of the Commercial Company "Luis Eduardo Guerrero Luzuriaga," managed by the owner, located in the city of Catamayo, during the period from October 1st to December 31st, 2023. The work is based on a mixed research approach, exploratory-descriptive in nature, implementing a non- correlational research design, employing the scientific method and various research techniques. To fulfill the stated objectives, a specific study of the nature of the business was conducted, serving as the basis for developing a coded plan and chart of accounts, establishing accounts corresponding to assets, liabilities, equity, revenues, costs, and expenses. Likewise, an initial inventory was prepared through a physical verification of assets, values, rights, and obligations, which allowed for the preparation of the Initial Balance Sheet, determining assets of $260,803.15, liabilities of $15,730.78, and equity of $245,072.37. Subsequently, auxiliary records for purchases and sales, accounts receivable, accounts payable, and payroll were designed to facilitate the recording of economic transactions: through the compilation of information, the accounting process was elaborated by recording each transaction in the journal applying a multiple account system, a process that led to the preparation of the general ledger, trial balance, worksheet with respective adjustments, and Financial Statements. Upon the conclusion of the Curricular Integration Work, the relevance of having an accounting organization is determined, as the processes and techniques applied allow for better control and knowledge, reflected in the positive result of the exercise with a net income of $29,143.43.